Solution of Extended Kelvin-Voigt Model - Karaś, Sławomir (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The great usefulness of uniaxial visco-elastic models, especially in highway engineering pavement theory, composites and other civil engineering disciplines were the reason for undertaking the trial to find a complete solution for the generalization of Kelvin-Voigt body. Here the elements of higher rank than velocities of strain and stress are considered. Carson’s transformation simultaneously with residuum theorem are used for solutions derivation. The introduced procedure can be also used for more complicated differential or integral forms of constitutive equations, as well as for non homogenous initial conditions. The Burgers’ body is examined. Finally, as an example the vibration of simple beam is shown.